2016
DOI: 10.3847/0004-637x/818/2/194
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal of Tidal Debris in a Milky-Way-Sized Dark Matter Halo

Abstract: We simulate the tidal disruption of a collisionless N-body globular star cluster in a total of 300 different orbits selected to have galactocentric radii between 10 and 30 kpc in four dark matter halos: (a) a spherical halo with no subhalos, (b) a spherical halo with subhalos, (c) a realistic halo with no subhalos, and (d) a realistic halo with subhalos. This allows us to isolate and study how the halo's (lack of) dynamical symmetry and substructures affect the dispersal of tidal debris. The realistic halos ar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 56 publications
0
29
1
Order By: Relevance
“…However, fundamental caveats still persist and should be addressed in follow-up works. For instance, our models are a superposition of not only smooth but also static potentials, and substructure (such as dark matter subhaloes: Ibata et al 2002;Carlberg 2009;Yoon et al 2011;Carlberg 2015;Erkal & Belokurov 2015a,b;Erkal et al 2016;Ngan et al 2016;Erkal et al 2017) as well as time-dependence (Manos et al 2013;Manos & Machado 2014;Hattori et al 2016;Machado & Manos 2016;Monari et al 2016;Price-Whelan et al 2016b;Erkal et al 2017;Pearson et al 2017, and references therein) could enhance the efficiency of diffusion in phase space (Peñarrubia 2013). It is worth noticing that sources of noise, such as scattering by short-scale irregularities, or periodic driving given by external coupling can, indeed, enhance the diffusion rate of sticky orbits (see Habib et al 1997;Kandrup et al 2000;Siopis & Kandrup 2000;Kandrup & Sideris 2003;Kandrup & Siopis 2003, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…However, fundamental caveats still persist and should be addressed in follow-up works. For instance, our models are a superposition of not only smooth but also static potentials, and substructure (such as dark matter subhaloes: Ibata et al 2002;Carlberg 2009;Yoon et al 2011;Carlberg 2015;Erkal & Belokurov 2015a,b;Erkal et al 2016;Ngan et al 2016;Erkal et al 2017) as well as time-dependence (Manos et al 2013;Manos & Machado 2014;Hattori et al 2016;Machado & Manos 2016;Monari et al 2016;Price-Whelan et al 2016b;Erkal et al 2017;Pearson et al 2017, and references therein) could enhance the efficiency of diffusion in phase space (Peñarrubia 2013). It is worth noticing that sources of noise, such as scattering by short-scale irregularities, or periodic driving given by external coupling can, indeed, enhance the diffusion rate of sticky orbits (see Habib et al 1997;Kandrup et al 2000;Siopis & Kandrup 2000;Kandrup & Sideris 2003;Kandrup & Siopis 2003, and references therein).…”
Section: Discussionmentioning
confidence: 99%
“…Amorisco et al (2016), however, argued that giant molecular clouds could also be responsible for some of the fluctuations, and Ibata et al (2016) reported a null detection using the same stream. Currently undetected stellar streams may provide more information about dark substructure around the MW (Ngan et al 2016). Around larger, more distant galaxies, dark substructures may be revealed by gravitational lensing anomalies from background sources (Mao & Schneider 1998;Dalal & Kochanek 2002;Vegetti et al 2010;MacLeod et al 2013;Nierenberg et al 2014;Hezaveh et al 2016), particularly with the upcoming instruments on the James Webb Space Telescope (JWST ; MacLeod et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Ackermann et al 2014;Bringmann et jorpega@roe.ac.uk al. 2014) to detecting gaps in narrow tidal streams induced by close encounters with individual subhaloes (Ibata et al 2002;Johnston et al 2002;Yoon et al 2011;Carlberg 2013;Erkal & Belokurov 2015;Ngan et al 2016, Erkal et al 2016Bovy et al 2017), with no unambiguous results to date. Strongly-lensed galaxies provide complementary constraints on the clumpiness of dark matter haloes in the inner-most region of galaxies (Koopmans 2005;Vegetti & Koopmans 2009;Li et al 2013;Vegetti et al 2014).…”
Section: Introductionmentioning
confidence: 99%